FREEZER TEMPERATURE MONITOR AND ALARM - RAMAKRISHNAN, K; VIJAYABHARATHI, K; SIVADAS, T K (Fishery Technology, 2017)
An electronic instrument for measuring freezer temperature in the range of + 40 to -40°C is described. The salient features of the instrument are, remote display, (digital and analogue versions with an accuracy of ± 0.1 and ± 0.5°C respectively), and provision for continuous record of temperature. Two types of sensors using thermistor and P. N. junction of transistor were used for temperature sensing